Pernikahan Beda Agama Perspektif Hukum Islam dan Undang-undang Nomor 39 Tahun 1999 (Studi di Kecamatan Sukawati Kabupaten Gianyar Provinsi Bali) - Sholihuddin Sholihuddin; Ahmad Afan Zaini (Dikelola dan diterbitkan oleh Fakultas Syariah bekerja sama dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
Bali is one of the provinces in Indonesia with a fairly dense population. Bali is also known for being one of the leading natural tourism centers in Indonesia. Apart from tourism issues, Bali Province has one interesting issue to discuss. Bali is also an example of a place where inter-religious harmony has a fairly high portion. So there is rarely friction between religious communities in Bali. On the other hand, Bali, with its strong tourist charm, turns out to have several interesting problems. One example is the issue of interfaith marriages that are rife in Bali. Interfaith marriages are certainly not compatible with Islamic law or sharia, as well as conventional legal approaches or state law. It is interesting to discuss that many conversions of religious beliefs in Bali were carried out because to fulfill the requirements of the pillars of shah in Islam. Some from Hindus converted to Islam, some from Christians converted to Islam. This is another phenomenon that occurs in Bali besides a strong tourist attraction when discussing the island of the gods. Under these conditions, the authors conducted research on interfaith marriages in Bali, namely in Sukawati District, Gianyar Regency, Bali Province. Many religious marriage practices take place in that place. Some are local, some are doing interfaith marriages with foreign tourists visiting Bali.